Birth Asphyxia Is Associated With Increased Risk of Cerebral Palsy: A Meta-Analysis - Zhang, Shan; Li, Bingbing; Zhang, Xiaoli; Zhu, Changlian; Wang, Xiaoyang (Frontiers in Neurology, 2020)
Objective: To assess the association between birth asphyxia – as measured by the pH of umbilical cord blood – and cerebral palsy in asphyxiated neonates ≥35 weeks’ gestation. Methods: Two reviewers independently selected English-language studies that included data on the incidence of cerebral palsy in asphyxiated neonates ≥35 weeks’ gestation. Studies were identified from the PubMed, Google Scholar, Embase, and Cochrane Library databases up to 31 December 2019, and the reference lists of the retrieved articles were screened. Results: We identified 10 full journal articles that met the inclusion criteria for entry into the meta-analysis, including 8 randomized controlled trials and 2 observational studies. According to a random effects model, the pooled rate of cerebral palsy in the randomized controlled trials was 20.3% (95% CI: 16.0–24.5), and the incidence of cerebral palsy in the observational studies was 22.2% (95% CI: 8.5–35.8). Subgroup analysis by treatment for hypoxic ischemic encephalopathy in asphyxiated neonates showed that the pooled rates of cerebral palsy were 17.3% (95% CI: 13.3–21.2) and 23.9% (95% CI: 18.1–29.7) for the intervention group and non-intervention group, respectively. Conclusion: Our findings suggest that the incidence of cerebral palsy in neonates (≥35 weeks’ gestation) with perinatal asphyxia is significantly greater than in the healthy neonate population. With the growing emphasis on improving neonatal neurodevelopment and reducing neurological sequelae, we conclude that the prevention and treatment of perinatal asphyxia are essential for preventing the development of cerebral palsy.